Architectural design and the brain: Effects of ceiling height and perceived enclosure on beauty judgments and approach-avoidance decisions. (March 2015) - Vartanian, Oshin; Navarrete, Gorka; Chatterjee, Anjan; Fich, Lars Brorson; Gonzalez-Mora, Jose Luis; Leder, Helmut; Modroño, Cristián; Nadal, Marcos; Rostrup, Nicolai; Skov, Martin
Abstract: We examined the effects of ceiling height and perceived enclosure—defined as perceived visual and locomotive permeability—on aesthetic judgments and approach-avoidance decisions in architectural design. Furthermore, to gain traction on the mechanisms driving the observed effects, we employed functional magnetic resonance imaging (fMRI) to explore their neural correlates. Rooms with higher ceilings were more likely to be judged as beautiful, and activated structures involved in visuospatial exploration and attention in the dorsal stream. Open rooms were more likely to be judged as beautiful, and activated structures underlying perceived visual motion. Additionally, enclosed rooms were more likely to elicit exit decisions and activated the anterior midcingulate cortex (aMCC)—the region within the cingulate gyrus with direct projections from the amygdala. This suggests that a reduction in perceived visual and locomotive permeability characteristic of enclosed spaces might elicit an emotional reaction that accompanies exit decisions. Highlights: Rooms with higher ceilings were more likely to be judged as beautiful than rooms with lower ceilings. Rooms with higher ceilings activated visuospatial exploration structures in the dorsal stream. Open rooms were more likely to be judged as beautiful than enclosed rooms. Open rooms activated structures underlying perceived visual motion. Enclosed rooms elicited exit decisions and activated a cingulate region connected with amygdala.